The effect of geometric imperfections on the mechanical response of isotropic closed-cell plate lattices. (February 2023) - Ha, Chan Soo; Hsieh, Meng-Ting
Highlights: Imperfections degrade mechanical properties of the plate-lattices significantly. Randomly dispersed defects have larger effect than periodically distributed ones. Stretching-dominated behavior is preserved even with imperfections. Abstract: Cubic+octet plate-lattices, whose unit cell comprises plates aligned along simple-cubic and face-centered-cubic planes of crystal structures, have attracted scientists and engineers because of their isotropic, near-optimal mass-specific performance that reaches theoretical upper bounds on stiffness and strength at low density. While their structural efficiency has been recently examined analytically, numerically and experimentally, their sensitivity to geometric imperfections has remained elusive. Here, using finite element simulations, we present sensitivity of the macroscopic mechanical properties of the plate-lattices to two types of geometric imperfections: namely, periodically distributed defects, characterizing plate waviness and displaced intersections, and randomly dispersed defects, representing missing plates, observed in their additively manufactured samples. Our results show that the randomly dispersed imperfections lead to a greater reduction in the Young's modulus and yield strength than its counterpart across all relative densities under consideration, while their scaling relations with the relative density remains linear, confirming their structural efficiency attributed to stretching-dominated behavior even with the presence of the imperfections. This study sheds light on previously elusive sensitivity of the plate-lattices to the geometric imperfections and provides understanding of their defect-dependent mechanical performance. Graphical abstract: Image, graphical abstract